SPECT V/Q for the diagnosis of pulmonary embolism: protocol for a systematic review and meta-analysis of diagnostic accuracy and clinical outcome. Issue 4 (21st April 2018) - Le Roux, Pierre-Yves; Robin, Philippe; Tromeur, Cécile; Davis, Alexandra; Robert-Ebadi, Helia; Carrier, Marc; Couturaud, Francis; Le Gal, Grégoire; Salaun, Pierre-Yves
Abstract : Introduction: Single photon emission computed tomography ventilation/perfusion (SPECT V/Q) imaging has many proponents within the nuclear medicine community and has already largely replaced planar V/Q scintigraphy in daily practice for the diagnosis of pulmonary embolism (PE). However, the test is still described in clinical guidelines as an experimental test because of insufficient evidence. Methods and analysis: We will conduct a systematic review and a meta-analysis of diagnostic accuracy and management outcome studies involving patients evaluated with V/Q SPECT for suspected acute PE. We will search from inception to 19 December 2017 MEDLINE, Embase and the Cochrane Central Register of Controlled Trials for diagnostic accuracy studies, randomised controlled trials and observational cohort studies. Two reviewers will conduct all screening and data collection independently. The methodological quality and risk of bias of eligible studies will be carefully and rigorously assessed using the Quality Assessment of Diagnostic Accuracy Studies-2, the Cochrane Collaboration's tool and the Risk Of Bias In Non-randomised Studies - of Interventions (ROBINS-I) tools. The primary outcomes will be sensitivity, specificity and likelihood ratios of V/Q SPECT for the diagnosis of acute PE. The secondary outcomes will be the rate of venous thromboembolism during a 3-month follow-up period in patients left untreated after a negative diagnostic work-up based on SPECT V/Q. Ethics and dissemination: This study of secondary data does not require ethics approval. It will be presented internationally and published in the peer-reviewed literature. PROSPERO registration number: CRD42018084095.